Literatur Review : The Effect of Work Discipline and Compensation on Employee Performance through Work Motivation as an Intervening Variable at PT.Tata Bangun Sarana (Case Study on Marketing Department) - Jihan Shafira; Adi Wibowo Noor Fikri; Christophorus Indra Wahyu Putra (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This study aims to test and analyze the effect of work discipline and compensation on employee performance with work motivation as an intervening variable at PT. Tata Bangun Sarana. Respondents in this study were all marketing of PT Tata Bangun Sarana. Based on the saturated sample method, the total sample in this study was 95 respondents. In this study using primary data obtained from the distribution of questionnaires. The number of questionnaires distributed as many as 95 copies and which can be returned and processed as many as 95 eksempalar.